Analiza vladne racionalnosti v javnih politikah za obvladovanje epidemije covid-19 - Maraž, Denis (Monitor ISH, 2024)
During the Covid-19 epidemic, the government of the Republic of Slovenia, aiming to protect public health and save lives, implemented measures that infringed upon constitutionally protected democratic rights, such as the freedom of expression and the right to peaceful assembly. The government’s political communication, amid the disruption of normal life, facilitated the homogenization of a new reality while simultaneously serving to legitimize the management of the epidemic. In this paper I address the question of political rationality in government policies during the Covid-19 epidemic through an analysis of press conferences, the official communication channel of the government during this period. We approach the rethinking of the political response to the health crisis by examining how the emergence of the new SARS-CoV-2 virus and the covid-19 epidemic were problematized, or rather, the way in which this phenomenon was framed as a socio-political problem. In this context, we are interested in the effects that this problematization had on both society and the individual. In interpreting the government’s reasoning behind the measures, we draw on the concept of political rationality, which both enabled and simultaneously legitimized the government’s conduct.
Keywords: Covid-19; covid-19 pandemic; Demokracija; Demonstracije; Foucault; Foucault, Michel; notranja politika; oblast; pandemije; political rationality; power; problematization; Slovenija; vladni ukrepi